Perlindungan Hukum Terhadap Data Pribadi Nasabah Layanan Perbankan Setelah Berlakunya Peraturan Otoritas Jasa Keuangan (POJK) Nomor 6/Pojk.O7/2022 - Raissa Avila Nasution; Budiman Ginting; Mahmul Siregar; Tengku Keizerina Devi Azwar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article or writing aims to analyze the legal protection of personal data for banking customer services and analyze the resolution of the problem of leakage and protection of customer data after the enactment of financial services authority regulation (POJK) Number 6/Pojk.O7/2022. The problem focuses on the Financial Services Authority (OJK) regulations and the Personal Data Protection Law (UU PDP). Data was collected using a normative approach, using primary (laws, regulations), secondary (legal literature), and tertiary (legal encyclopedia) legal materials, and analyzed qualitatively. The research results show that the protection of banking customers' personal data in Indonesia has increased with the existence of POJK Number 6/POJK.07/2022 and Law Number 27 of 2022, which emphasize transparency, transparency and data security. Banking institutions must comply with the provisions and sanctions if they violate them, with the OJK playing an important role in supervision. In addition, resolving data leaks involves assessing losses and can be done through mediation, arbitration or litigation. Compliance with regulations and principles of legal justice is expected to minimize negative impacts and maintain public trust.